»Jaz sem 16 % madžar in 50 % slovenec in 80 % anglež.« Jezikovni portreti petošolcev na narodnostno mešanih območjih - Tibaut, Katarina; Lipavic Oštir, Alja (Revija za elementarno izobraževanje, 2021)
“I am 16% Hungarian and 50% Slovene and 80% English.” Language Portraits of Fifth-grade Elementary School Students from Nationally Mixed Areas. In this article, which originated as part of the project “Jeziki štejejo” (Languages matter), we discuss the differences in perception of individual languages, expressed through language portraits created by fifth-grade elementary school students. Special attention was paid to the comparison of portraits between pupils in nationally diverse regions (Slovenian Istria and Prekmurje) and pupils in other parts of the country. The results of quantitative analysis of these language portraits reveal statistically relevant differences with regard to the school model. Differences were particularly evident in the choice of marked languages and the position of each individual language in the language portraits.
Keywords: language portraits; multilingualism; minority languages; elementary school; nationally mixed areas